Frequency domain approach to minimizing detectable faults in FDI systems - Frank, Paul M.; Ding, X. (Zielona Góra: Uniwersytet Zielonogórski)
Problems related to fault detection and isolation in uncertain dynamical systems are studied. The purpose of this study is to develop a scheme to design residual generators and furthermore to evaluate residuals. Different from the most of previous studies, the basic idea of this work is to minimize the size of detectable faults.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka